Development and Preclinical Evaluation of a Lyophilized Vaccine Against Equine Herpesvirus Type 4 (EHV-4) - Lespek Kutumbetov; Balzhan Myrzakhmetova; Aiganym Tussipova; Gulzhan Zhapparova; Talshyn Tlenchiyeva; Karina Bissenbayeva; Sergazy Nurabayev; Aslan Kerimbayev (Vaccines, 2025)
Background/Objectives: Equine rhinopneumonia, caused by equine herpesvirus types 1 and 4 (EHV-1 and EHV-4), continues to be a significant health and economic concern in the global equine industry, particularly in Kazakhstan. While vaccines targeting EHV-1 are available, there is currently no licensed monovalent vaccine for EHV-4, and existing formulations offer limited protection against this serotype. This study aimed to develop and evaluate a freeze-dried, live-attenuated EHV-4 vaccine with improved safety, stability, and immunogenicity. Methods: A field isolate of EHV-4 was attenuated through serial passaging in primary lamb testicle (LT-KK49) cell cultures. Viral biomass was concentrated and formulated with various stabilizers before freeze-drying. The most effective stabilizer composition—sucrose, gelatin, and lactalbumin hydrolysate—was selected based on viral titer retention. Safety and immunogenicity were assessed in mice, guinea pigs, rabbits, donkeys, and horses. A guinea pig reproductive challenge model was used to evaluate protective efficacy. Results: The optimized lyophilized vaccine retained infectivity (>6.0 log10 TCID50/cm3) for at least six months at 4 °C. No adverse clinical signs were observed in any test species. Immunization induced robust neutralizing antibody responses in both small animals and equines. In the guinea pig model, vaccinated females demonstrated 100% pregnancy retention and fetal viability following challenge with a virulent EHV-4 strain. Conclusions: This freeze-dried, live-attenuated EHV-4 vaccine candidate is safe, immunogenic, and thermostable. It offers a promising platform for the targeted prevention of EHV-4 infection, particularly in young horses and in regions with limited cold-chain infrastructure.